¿PCB o PCdoB? Perspectivas chinas sobre la ruptura comunista en Brasil, 1962 - Leonardo Barbosa (Nuevo mundo - Mundos Nuevos)
The 1960s, with the domestic and international turbulence of the Cold War, represented a turning point for the relationship between Brazil and the People's Republic of China (PRC). This article analyses how the Communist Party of China (CCP) understood the split between the Brazilian Communist Party (PCB) and the Communist Party of Brazil (PCdoB) in 1962. Through detailed analysis of articles and editorials in the People's Daily, the official newspaper of the CCP, this research provides valuable insights into the priorities of the CCP, its strategic objectives and its efforts to shape the internal perception of political developments in Brazil. Ultimately, the Goulart government of 1961-1964 presented itself as an opportunity for China to break out of its diplomatic isolationism, deepened by clashes with India and the Sino-Soviet split. In this context, the fracturing of the communist world was keenly observed in Brazil by the Chinese media, which waged an ideological battle in the pages of the People's Daily. In the end, the paper made it clear that the PCdoB and its members had the ideological superiority, while Carlos Prestes and the PCB had fallen prey to Khrushchev’s revisionism.